Peningkatan Kemandirian Anak Usia 4-5 Tahun Melalui Bercerita - Mariana Ikun RD Pareira; Naomi Habi Atal (Universitas Trunojoyo Madura, 2019)
Autonomy is important to be taught early because makes it will easier for children to carry out further education. Autonomy also leads children to have high self-esteem and intrinsic motivation. The most prominent problem in children at TK Tunas Harapan Emaus Liliba Kupang is autonomy. Autonomy can be promoted in various ways, one of them which is story telling. The purpose of this study is to find out whether there is an increase in autonomy of children ages 4-5 years after story telling. The research method used in this research is experimental method with quantitative approach. The research design used is a non-equivalent research design or also called